IoT Based ıntegrated smart home automatıon system - Satheeskanth, N.; Marasinghe, S.D.; Rathnayaka, R.M.L.M.P.; Kunaraj, A.; Joy Mathavan, J. (Research gate, 2022)
The comfort of human in home can be categorized under several types. Among these categories, the most significant ones are the thermal comfort, which is related to ambient temperature and humidity, followed by the visual comfort, related to room’s colors and lightning, and hygienic comfort, associated with air quality. All these conditions can be monitored within the acceptable range using home automation system. Automation can be accomplished using the Internet of Things (IoT). This gives the inhabitant accesses to certain data in the house and the ability to control some parameters remotely. This paper presents the complete design of an IoT based sensing and monitoring system for a smart home automation. This system use NodeMCU-ESP8266 microcontroller board for wireless communication, to provide the user with remote control of various appliances within their home and to store the data in the server.
Keywords: NodeMCU-ESP8266 Microcontroller; Arduino; Smart home; Home automation